Effect of credit constraint on yield: the case of ginger producers in southern and central Ethiopia - Tilore, Fetagn Gizachew; Shano, Berhanu Kuma; Shirko, Alula Tafesse; Hawitibo, Alemu Lambamo (Frontiers in Sustainable Food Systems, 2024)
Introduction This research investigates the impact of credit constraints on the yield of smallholder ginger farmers in southern and central Ethiopia. It addresses the importance of understanding the relationship between credit constraints and agricultural productivity in smallholder farming systems. Methods Employing a cross-sectional dataset from 343 randomly selected households, we utilized the endogenous switching regression model to address potential sample selection bias. Results The analysis in the first stage showed that livestock holding, marital status, farm size, distance to credit source, and information access are primary determinants influencing the credit constraint status of smallholder ginger farmers. In the second stage, the analysis revealed that family size, farm size, and cooperative membership significantly affected ginger yield. Moreover, the average treatment effect suggests a significant impact of credit constraints on ginger yield, with credit-constrained farmers experiencing a greater positive effect compared to credit-unconstrained farmers. These findings highlight the complex relationships between credit constraints, socioeconomic factors, and agricultural yield in the context of smallholder ginger farming. Discussion The implications of this research extend to informing policy decisions and intervention strategies aimed at alleviating credit constraints and enhancing the overall yield and livelihoods of smallholder ginger farmers in the studied regions. Policy recommendations include prioritizing interventions to enhance ginger yield by promoting cooperative membership, improving access to credit sources, fostering livestock ownership, and reducing the distance to credit sources. Additionally, enhancing access to information for effective mitigation of credit constraints is crucial for boosting productivity in smallholder ginger farming.